The Role of the City Government in Flood Mitigation and Control in Medan City - Muhaimin, Muhammad Farhan (Asian Journal of Multidisciplinary Research, 2025)
This study explores the strategic role of the Medan City Government in addressing and controlling the chronic issue of flooding, which has widespread social, economic, and political impacts. Flooding in Medan disrupts education, increases health risks, causes economic losses for SMEs, and reduces public trust in the government. Using a qualitative descriptive approach, the study gathers data through in-depth interviews, direct observations, and policy document analysis. The study applies Riant Nugroho’s public policy theory and Miftah Thoha’s role theory to assess the effectiveness of flood management policies, identifying obstacles such as budget constraints, poor inter-agency coordination, and low community participation. The findings aim to provide strategic recommendations to enhance government capacity, improve coordination, and increase public involvement in flood mitigation, contributing to the development of a sustainable flood management policy model for urban areas.